Facilitating vocabulary learning through metacognitive strategy training and learning journals - Trujillo Becerra, Carmen Luz; Álvarez Ayure, Claudia Patricia; Zamudio Ordoñez, Mirtha Nohemí; Morales Bohórquez, Gloria (Colombian Applied Linguistics Journal, 2015)
This paper reports on a mixed-method action research study carried out with participants from three public high schools in different regions in Colombia: Bogotá, Orito, and Tocaima. The overall aim of this study was to analyze whether training in the use of metacognitive strategies (MS) through learning journals could improve the participants’ vocabulary learning. The data, collected mainly through students’ learning journals, teachers’ field notes, questionnaires and mind maps, was analyzed following the principles of grounded theory. The results suggested that the training helped participants to develop metacognitive awareness of their vocabulary learning process and their lexical competence regarding daily routines. Participants also displayed some improvements in critical thinking and self-directed attitudes that could likewise benefit their vocabulary learning. Finally, the study proposes that training in metacognitive and vocabulary strategies should be implemented in language classrooms to promote a higher degree of student control over learning and to facilitate the transference of these strategies to other areas of knowledge.